LITERATURE REVIEW AND ANALYSIS OF RESEARCH CONDUCTED IN EUROPE ON HEALTH LITERACY - Brodowska-Szewczuk, Jolanta (Management and Administration Journal, 2024)
According to World Health Organization, Health Literacy encompasses the cognitive and social skills that determine the motivation and ability of individuals to access, understand and use information in a way that promotes and maintains good health. The aim of this article is to present the concept of “health literacy”, its determinants and consequences, as well as to review research conducted in Europe using the European Health Literacy Survey Questionnaire – HLS-EU-Q16 indicator. For this purpose, a literature review was conducted, to incorporate analysis and criticism. The article determines the scope of research on health literacy in Europe using the European Health Literacy Survey Questionnaire – HLS-EU-Q16, based on literature analysis. The greater people’s health literacy, the better their understanding of prevention and treatment. Low health awareness means financial losses, both personal and global. High Health Literacy enables good prevention, which is the best and cheapest method in every health system.